Answer:
The transformation was a dilation with scale factor 1/3
Explanation:
we know that
The transformation
Y ------> Y'
is equal to
Y(-9, 6) -----> Y'(-3, 2)
Divide the x-coordinate of the image by the x-coordinate of the pre-image
-3/-9=1/3
Divide the y-coordinate of the image by the y-coordinate of the pre-image
2/6=1/3
The scale factor is equal to k=1/3
The rule of the transformation is equal to
![(x,y) ------> (kx,ky)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pb2ybz2u6b6u05pek3z0j0s5khlxj5uwea.png)
![(x,y) ------> ((1)/(3)x,(1)/(3)y)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bmw017cgb4r47608ysdg5viuxyqt9i9rdm.png)
therefore
The transformation was a dilation with scale factor 1/3